1993
DOI: 10.1007/bf02251203
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors on the occurrence of response fluctuations and dyskinesias in Parkinson's disease

Abstract: We studied the risk factors that influence the occurrence of response fluctuations and dyskinesias in 194 patients with Parkinson's disease (PD). These factors included age at onset, disease severity at levodopa initiation, duration of illness prior to levodopa therapy and the daily dose of levodopa at the end of study. The first three were fixed covariates and the last one was time-dependent. Patients with age onset before 50 years showed a higher risk of developing response fluctuations (RF) and dyskinesias … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Several studies have also shown that the dyskinesias and the motor fluctuations correlated with the duration of levodopa treatment rather than the duration of the disease (Rajput et al ., 1984; Leenders et al ., 1986; Melamed, 1986; Denny and Begari, 1999; Grandas et al ., 1999), although others failed to prove such relationship (Fahn and Bressman, 1984; Horstink et al ., 1990; Fahn, 1996). The exact contribution of the levodopa dose remains controversial (Fahn and Bressman, 1984; Peppe et al ., 1993; Wu et al ., 1993), but a chronic low dose regimen has been linked to a lower incidence of dyskinesias (Rajput et al ., 1984; Poewe et al ., 1986). Three groups of patients in our study did not differ significantly in daily doses of levodopa at the emergence of dyskinesias (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also shown that the dyskinesias and the motor fluctuations correlated with the duration of levodopa treatment rather than the duration of the disease (Rajput et al ., 1984; Leenders et al ., 1986; Melamed, 1986; Denny and Begari, 1999; Grandas et al ., 1999), although others failed to prove such relationship (Fahn and Bressman, 1984; Horstink et al ., 1990; Fahn, 1996). The exact contribution of the levodopa dose remains controversial (Fahn and Bressman, 1984; Peppe et al ., 1993; Wu et al ., 1993), but a chronic low dose regimen has been linked to a lower incidence of dyskinesias (Rajput et al ., 1984; Poewe et al ., 1986). Three groups of patients in our study did not differ significantly in daily doses of levodopa at the emergence of dyskinesias (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Other risk factors are an early age at disease onset and a high cumulative dose and duration of levodopa treatment (Grandas et al, 1999;Sharma et al, 2010;Wu et al, 1993). It has also been reported that females have a higher risk of this motor complication, although this is not consistent across studies (Lyons et al, 1998;Van Garpen et al, 2006;Zappia et al, 2005).…”
Section: Clinico-demographic Factorsmentioning
confidence: 94%
“…In addition to the increased likelihood that younger‐onset patients with PD are male,36‐38,41 younger‐onset PD patients also experience more extrapyramidal motor side effects when treated,36,41‐45 suggesting an elevated susceptibility of the basal ganglia to treatment‐associated toxicity. Like PD, DLB also has a male predominance in younger age cohorts (under 70)46 and the presence of extrapyramidal symptoms is one of the diagnostic criteria used in diagnosing DLB.…”
Section: Introductionmentioning
confidence: 99%